Persepsi Masyarakat Terhadap Keberadaan Ekowisata Mangrove Di Kecamatan Setia Bakti Kabupaten Aceh Jaya - Edi Saputra; Elly Susanti; Mujiburrahmad Mujiburrahmad (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Setia Bakti Subdistrict, West Aceh is one of the areas where there are many mangrove forest ecosystems. Mangrove ecosystems have very important ecological, socio-economic, and socio-cultural roles. Therefore, mangrove forests are used as mangrove ecotourism. One of the factors needed to improve ecotourism objects is public perception. The purpose of this study was to find out how the public's perception of the existence of mangrove ecotourism and what factors influence it. This research uses descriptive method and multiple linear analysis. The results of this study indicate that community perceptions of mangrove ecotourism are generally good and influenced by age, education level, occupation and distance of residence. The factor that significantly influences people's perceptions is the level of education with a regression coefficient of 0.052.